Pengaruh Cyberbullying di Media Sosial Terhadap Kepercayaan Diri Remaja Akhir di Kota Kupang - Assan, Maria Cahyani Samantha; Keraf, M.K.P Abdi; Uda, Paulinus A. S.; Apriliana, I Putu Agus (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2024)
This study aims to determine (1) the description of cyberbullying experienced by adolescents, (2) the description of self-confidence of adolescents, and (3) the investigation of the influence of cyberbullying on social media on adolescents’ self-confidence. This research uses a quantitative approach with an ex-post facto type. A total of 154 adolescents aged 17-20 years and active social media users were involved. Data analysis techniques use descriptive analysis and simple linear regression tests with SPSS Applications. The research findings show that teenagers' cyberbullying experience is in the low category (66%) and their level of self-confidence is in the medium category (64%). There is a significant negative influence between cyberbullying and self-confidence. These findings show that the higher the cyberbullying experienced, the lower the adolescent's self-confidence. Future researchers are expected to pay attention to other factors that influence self-confidence, then be able to specifically choose social media that is used as a means for carrying out cyberbullying as well as cyberbullying behavior in terms of gender.